The Relationship Between the Role of Parents to the Growth of Preschool Children in Kalimati Village, Tarik District Sidoarjo - Erma Retnaningtyas; Arina Chusnatayaini; Vidia Atika Manggiasih; Shanty Natalia; Sri Yulis Setyaningsih (Universitas STRADA Indonesia, 2023)
Growth and development are processes that occur in living things. Growth is said to increase in physical size, due to the multiplication of cells and the increasing number of substances between cells. Growth and development concern all aspects of progress achieved from the womb to adulthood (Irianton Aritonang, 1996). Based on an initial survey with interview techniques for 10 respondents conducted at the Posyandu Kalimati in January 2020 showed that there are still many toddlers with poor nutritional status. The purpose of this study was to Analyze the Relationship of the Role of Parents to the Growth of Preschool Children in Kalimati Village, Tarik Sidoarjo District in 2020. The design of this study included a cross sectional analytic study with a survey approach. The population in this study were all parents and toddlers in the Kalimantan village of Tarik Sidoarjo in 2020, amounting to 30 respondents.